MODEL KECEPATAN 1D GELOMBANG P DAN RELOKASI HIPOSENTER WILAYAH SULAWESI UTARA DAN SEKITARNYA MENGGUNAKAN METODE COUPLE VELOCITY-HYPOCENTER - Christi Tumangkeng; Donny Royke Wenas; Sixtus Iwan Umboh (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
North Sulawesi is in a complex tectonic interaction which is the relative movement of three Eurasian macro plates, the Pacific plate, the Philippine plate, and the Maluku Sea microplate. The active tectonic movement results in high earthquake activity in the region of North Sulawesi and its surroundings. This results in the importance of accurate earthquake parameter information, one of which is by conducting research on local wave velocity. The purpose of this study is to determine the velocity of 1D P waves and relocate the earthquake hypocenter and determine the correction stations in North Sulawesi and surrounding areas with coordinate boundaries 0.17166°S- 2.742781°N and 119.5212°E- 125.5067°E using the Couple Velocity-Hypocenter method with Velest software. The results of simultaneous inversion processing are carried out until the 50th iteration which obtains the wave velocity fluctuates at several depths but in general, the denser layers of the earth's compilers will increase the wave velocity, the improvement of the RMS from an average of 1.71 to 0.49 and the correction of the stations obtained is at intervals of 0.39 to 20.91.